Case report: Success of allogeneic hematopoietic stem cell transplantation for refractory systemic-onset juvenile idiopathic arthritis - Beaufils, Camille; Proulx, Catherine; Blincoe, Annaliesse; Teira, Pierre; Bittencourt, Henrique; Cellot, Sonia; Duval, Michel; Morin, Marie-Paule; De Bruycker, Jean Jacques; Couture, Julie; Samaan, Kathryn; Decaluwe, Hélène; et al. (Frontiers in Medicine, 2023)
Objectives This study reports cases of systemic-onset juvenile idiopathic arthritis (sJIA) who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) at our center and reviews published outcomes of allo-HSCT in sJIA. Methods We present a case report of two patients with sJIA who underwent allo-HSCT at a tertiary pediatric hospital. Each patient’s disease course and allo-HSCT protocol/outcome are described. Outcomes of published cases of allo-HSCT in sJIA were compared to our experience. Results Two patients with sJIA had allo-HSCT. Both failed multiple lines of disease-modifying anti-rheumatic drugs and experienced severe disease/treatment-related complications. Despite post-HSCT complications, both recovered without sequelae. Five years post-HSCT, patient 1 is in complete remission (CR) and is off medications. Patient 2 was in CR until 11 months post-HSCT after which he developed three disease flares. At 4 years post-HSCT he is currently in CR on Adalimumab monotherapy. Engraftment was excellent with a donor chimerism of 100% for patient 1 and 93% for patient 2. In the literature, the outcome of allo-HSCT is reported in 13 sJIA patients. When merging those with our 2 patients, 1/15 patients died and 13/14 achieved CR, of which 12 are off medications (median [range] follow-up: 2.2 [0.2–7.0] years). Extended follow-up data on 11 of the 13 reported sJIA patients showed that an additional 3 patients flared at 3, 4, and 10 years post-HSCT. Conclusion We report two patients with severe/refractory sJIA who underwent successful allo-HSCT and achieved CR. Allo-HSCT is a potential curative option for severe/refractory sJIA. It should be considered only after failure of conventional sJIA treatments and when an HLA-matched donor is available in order to lower transplant-related mortality. The outcomes of reported sJIA patients who received allo-HSCT are encouraging but long-term follow-up data are needed to better characterized the risk–benefit ratio of this procedure.